Intratympanic steroid therapy for Bell’s palsy with poor prognostic results - Akira Inagaki (Nature Portfolio, 2021)
Abstract In Bell’s palsy, electrodiagnosis by electroneurography (ENoG) is widely used to predict a patient’s prognosis. The therapeutic options for patients with poor prognostic results remain controversial. Here, we investigated whether early intervention with intratympanic steroid therapy (ITST) is an effective treatment for Bell’s palsy patients with poor electrodiagnostic test results (≤ 10% electroneurography value). Patients in the concurrent ITST group (n = 8) received the standard systemic dose of prednisolone (410 mg total) and intratympanic dexamethasone (16.5 mg total) and those in the control group (n = 21) received systemic prednisolone at the standard dose or higher (average dose, 605 ± 27 mg). A year after onset, the recovery rate was higher in the ITST group than in the control group (88% vs 43%, P = 0.044). The average House-Brackmann grade was better in the concurrent ITST group (1.13 ± 0.13 vs 1.71 ± 0.16, P = 0.035). Concurrent ITST improves the facial nerve outcome in patients with poor electroneurography test results, regardless of whether equivalent or lower glucocorticoid doses were administered. This may be ascribed to a neuroprotective effect of ITST due to a higher dose of steroid reaching the lesion due to dexamethasone transfer in the facial nerve.